Hungarian Monitoring, 20 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports from Prague - Correspondence on Poland Domestic Affairs: - Mass rallies celebrating August 20: speeches by Miklós Németh, Mátyás Szűrös, Rezső Nyers - Károly Grósz plans to retire, says Hungarian Socialist Workers' Party (MSZMP) Political Administration Committee member Pál Iványi - Hungarian Democratic Forum (MDF) rallies: István Csurka emphasizes that his organization does not want violent change - Saint Stephen's Day celebrations in front of Basilica attended by tens of thousands - Debate evening between Hungarian Democratic Forum (MDF) and Hungarian Socialist Workers' Party (MSZMP) - Hungarian Socialist Workers' Party (MSZMP)'s Margit Island debate forum Külpolitika: - Prágai beszámoló - Lengyelországi tudósítás Belpolitika: - Augusztus 20-i ünnepi nagygyűlések: Németh Miklós, Szűrös Mátyás, Nyers Rezső beszédei - Grósz Károly azt tervezi, hogy nyugdíjba vonul - Mondta az MSZMP Politikai Intézőbizottságának tagja, Iványi Pál - MDF nagygyűlések. CSURKA I. megerősítette, szervezete nem akar erőszakos változást - Szent István napi ünnepségek a Bazilika előtt, amelyen tízezrek vettek részt - Az MDF és az MSZMP vitaestje - MSZMP Margit-szigeti fórumáról